2007
DOI: 10.1253/circj.71.226
|View full text |Cite
|
Sign up to set email alerts
|

Late Angiographic Stent Thrombosis After Sirolimus-Eluting Stent Implantation

Abstract: Background Although drug-eluting stents dramatically reduce revascularization after percutaneous coronary intervention (PCI), it is still unclear whether they increase the risk of stent thrombosis. Late stent thrombosis (>30 days) was a very rare complication after bare metal stent implantation. Four cases of confirmed late angiographic stent thrombosis (LAST) after sirolimus-eluting stent (SES) implantation are presented and the incidence, promoting factors and outcomes of such cases in Japan, where clopidogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…QCA was performed in only half of the patients at the independent core laboratory. In conclusion, this study showed acceptable results with SES with aspirin plus low dose of ticlopidine (200 mg/day) compared to other registry studies with aspirin plus clopidogrel [2][3][4][5]7,8,[24][25][26][27][28][29][30][31][32][33] although approximately half of the patients quitted ticlopidine within 1 year mainly due to side effects. Low dose of ticlopidine administration might be a cost-effective substitute of clopidogrel after SES implantation in Japanese populations.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…QCA was performed in only half of the patients at the independent core laboratory. In conclusion, this study showed acceptable results with SES with aspirin plus low dose of ticlopidine (200 mg/day) compared to other registry studies with aspirin plus clopidogrel [2][3][4][5]7,8,[24][25][26][27][28][29][30][31][32][33] although approximately half of the patients quitted ticlopidine within 1 year mainly due to side effects. Low dose of ticlopidine administration might be a cost-effective substitute of clopidogrel after SES implantation in Japanese populations.…”
Section: Discussionmentioning
confidence: 53%
“…Despite treating high risk lesions with low dose ticlopidine, J-PMS data showed event rates are equal to or lower than other studies in other countries. [2][3][4][5]7,8,[24][25][26][27][28][29][30][31][32][33] The rates at 1 year of definite and probable stent thrombosis, MACE and target vessel failure: 0.40%, 7.3% and 9.3% are acceptable because other registry studies showed these results ranged from 0.4% 3 to 1.3%; 22 5.8% 7 to 15%; 23 and 9.8% 3 to 12%, 21 respectively. [2][3][4][5]7,8,[24][25][26][27][28][29][30][31][32] Before the launch of the CYPHER stent in Japan, educational instruction courses were conducted all over the country to teach high maximal inflation pressure [34][35][36][37] and confirmation of stent full expansion with IVUS, if possible.…”
Section: Discussionmentioning
confidence: 95%
“…14 The incidence of stent thrombosis in the modern era of stent deployment varies from a low of 0.5% to 1.9% with BMS implantation, the same as with DES implantation. [15][16][17] To prevent stent thrombosis, clopidogrel 75 mg/day should be given for at least 6 months after DES implantation and, ideally, up to 12 months in patients who are not at high risk of bleeding, but there has been debate regarding how long such therapy should continue.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 A new concern beyond restenosis has arisen regarding the potential for late thromboses or very late thromboses after DES implantation, which limits discontinuation of the post-stent antiplatelet regimen. 6,7 These are rare, but lifethreatening, complications that should never be neglected and are in part caused by impaired endothelial regeneration; namely, reendothelialization, which is essential in the normal wound healing process of injured vessels and is affected by the drugs that coat the stent's surface. 8 Sirolimus and paclitaxel are potent anti-mitotic agents that strongly inhibit smooth muscle proliferation and matrix growth, preventing neointimal formation and restenosis.…”
mentioning
confidence: 99%